Total suspended matter, particulate organic matter and particulate inorganic matter from discrete water samples during RV MARIA S. MERIAN cruise MSM65 (2017-06-25 – 2017-07-19, GREENHAB II) - Voß, Daniela; Pieck, Daniela; Mascarenhas, Veloisa J; Zielinski, Oliver (PANGAEA, 2025)
This dataset was collected during the cruise MSM65 (GREENHAB II, 2017-06-25 – 2017-07-19) with RV MARIA S MERIAN from St. John's, Canada to Nuuk, Greenland. It contains measurements of total suspended particulate matter [mg/L], particulate organic matter [mg/L] and particulate inorganic matter [mg/L] from water samples collected via CTD. In total, 46 stations have been sampled from various depth. Water samples were filtered onboard through 0.7 μm pore size, glass fiber filters (Whatmann GF/F, 47mm) under low vacuum. Filters were frozen immediately at -25 °C until gravimetric analysis in laboratory according to IOCCG recommendations.
Keywords: Baffin Bay; Davis Strait; GREENHAB II; Greenland; Labrador Sea; North Atlantic Ocean; PIM; POM; SPM